Behavior of Th-isotopes along the pigment TiO2 industrial production process - Gazquez Gonzalez, M. (2015)
The present study, conducted initially to characterize from radiological point of view, the raw materials (ilmenite and titanium slag), co-products (copperas and sulfafer), wastes (red gypsum and ilmenite mud) and final product (TiO2) used/generated along the titanium dioxide industry, located in the province of Huelva, has allowed in addition a detailed study of the routes followed by several radionuclides, with special emphasis on Th-isotopes, throughout the industrial process. This pigment TiO2 industry works by the "sulphate method" which is a typical NORM (Naturally Occurring Radioactive Materials) industry. The raw material (ilmenite, mainly formed by FeTiO3), contains around 100 Bq kg-1 of U-series radionuclides, and around 400 Bq kg-1 from the Th-series ones. Along the industrial process, the secular equilibrium for the uranium and thorium series existing in the raw material is broken, and then the radionuclides are distributed/accumulated in the different materials according to their chemical behaviors. Therefore, the main goal of this study has been to gain basic information of the behavior of Th-isotopes in comparison with the behaviour of other natural radionuclides along the industrial process and, with basis in the information gained, to analyze the future potential environmental impact of co-products and wastes obtained in the industrial process. In this sense, it is important to note that some of the co-products (copperas and sulfafer) are currently used in fields such as, agriculture, fertilizers, etc. © 2014 by Nova Science Publishers, Inc. All rights reserved.